THE EFFECTIVENESS OF PRO-PEOPLE BUDGET IMPLEMENTATION: A STUDY ON THE GOVERNMENT OF WEST BANDUNG REGENCY - Wanda; Silviana (Kajian Akuntansi, 2025)
This study aims to examine the influence of Organizational Commitment, Budget Participation, and Leadership Style on the effectiveness of Pro poor Budgeting implementation in the Government of West Bandung Regency. The effectiveness of Pro poor Budgeting is crucial to ensure the budget allocation is targeted appropriately for poor and vulnerable communities. The research uses a quantitative approach with data collected through questionnaires distributed to 68 respondents from 34 regional government work units (SKPD) in West Bandung Regency. Data analysis is conducted using validity and reliability tests, along with multiple linear regression to test the hypotheses. The results show that all three variables simultaneously have a significant effect on the effectiveness of Pro poor Budgeting implementation, with a contribution of 95.7%. Individually, Organizational Commitment, Budget Participation, and Leadership Style also positively and significantly influence the effectiveness of the program. Organizational Commitment motivates employees to be responsible and innovative in budget management, while Budget Participation enhances ownership and accountability. Effective Leadership Style facilitates coordination and motivates employees in budget implementation. This study recommends that the Government of West Bandung Regency improve employee placement according to their competencies, provide flexibility in budget preparation, and strengthen program supervision to continuously enhance the effectiveness of Pro poor Budgeting.